Experimental study and characterization of chaos - Bai-lin, Hao (World Scientific, 1990)
Most of the review papers in this volume are based on lecture notes from ... the School on Experimental Study of Chaotic Phenomena, held in Tianjin, China, on 5-12 May [1989] ... and the Workshop on Condensed Matter, Molecular, and Atomic Physics, held at ... Trieste, Italy in June- August [1989]"